2021
DOI: 10.1039/d0ra10458b
|View full text |Cite
|
Sign up to set email alerts
|

A phytochemical-based medication search for the SARS-CoV-2 infection by molecular docking models towards spike glycoproteins and main proteases

Abstract: Identifying best bioactive phytochemicals from different medicinal plants using molecular docking techniques demonstrates a potential pre-clinical compound discovery against SARS-CoV-2 viral infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 57 publications
0
15
0
Order By: Relevance
“…α4, β5, β6, and α5 form a region named receptor-binding motif (RBM) and it includes most of the residues responsible for receptor binding [ 16 , 19 ]. A variety of inhibitors have been proposed for hindering ACE2-RBD interaction small inhibitors [ 48 ], antibodies [ 49 ], phytochemicals [ 50 ], and FDA-approved drugs [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…α4, β5, β6, and α5 form a region named receptor-binding motif (RBM) and it includes most of the residues responsible for receptor binding [ 16 , 19 ]. A variety of inhibitors have been proposed for hindering ACE2-RBD interaction small inhibitors [ 48 ], antibodies [ 49 ], phytochemicals [ 50 ], and FDA-approved drugs [ 51 , 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Afterwards, both the RMSD trajectories equilibrated and followed stable trajectories till the end of simulation. The protein-ligand complexes containing potential phytochemicals suggested by recent in-silico studies [ [59] , [60] , [61] , [62] , [63] , [64] ]⁠ also showed average RMSD values within ∼0.5 nm. The low RMSD values of complexes validated the stability of molecular docking poses.…”
Section: Resultsmentioning
confidence: 85%
“…Moreover, these traditional medicin alplantsexhibit multiple mechanisms of action, such as antiviral and immuno modulatory effects, as supported by insilico studies and other mechanistic studies. [58][59][60][61][62] Some of these Indian medicinal plants have already been evaluated in clinical studies around the world against SARS-CoV-2. For instance, Z. officinale and Echinacea intervention reduced symptoms such as coughing, shortness of breath, and muscular pain in suspected COVID-19 outpatients compared to hydroxychloroquine alone.…”
Section: Relevance In the Context Of Covid-19mentioning
confidence: 99%